ANALISIS KOREOGRAFI TARI JEPIN TEMBUNG PENDEK KARYA YUSUF DAHYANI KOTA PONTIANAK - Virgina Jannati, Delly Ariska; Istiandini, Winda; Fertisari, Ima (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research is to know the uniqueness that exist in Jepin Tembung Short Dance in Pontianak city of West Kalimantan. The purpose of this study is to describe the background of the creation of dance and the structure of Jepin Tembung Pendek dance with images to be clear and analyze the motion in each presentation of dance in order to be clearly understood about the presentation of Jepin Tembung Pendek dance.The method used is descriptive analysis with qualitative form. The approach used is Etnokoreologi. Research data in the form of observation, direct communication and documentary study of Jepin Tembung Pendek dance in Pontianak City. The result of this research is the effort done in analyzing the choreography of Jepin Shortcut dance dance that is meeting with resource person who is dancer and musician of Jepin Tembung Pendek dance in Pontianak City.Â Keywords: Choreography, Analysis, Jepin Tembung Pendek